OPTIMIZATION OF TRANSPORTATION COST IN SUPPLY CHAIN MANAGEMENT (SCM) - Rajesh A S, Subbaiah K M, Mohammed Ismail, Basavaraju. G (International Journal of Research Science and Management, 2015)
Transportation is movement of materials from origin to destination. In industrial means, expenses involved in moving materials/products from Supplier to Customer. Transport system is the most important economic activity among the components of business logistics systems. The data shows transportation is the highest cost, which occupies (one-third) of logistics costs, which includes order by inventory, warehousing cost, packing cost, management cost, movement cost and ordering cost. This paper deals with the reduction of transportation cost by adopting new technique. The analysis worked out in reduction of transportation cost to greater extent.